(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Agriculture is mostly dependent on rain water and it is affected by some climatic irregularities. Industry releases huge amount of wastewater each day and there is demand for irrigation, the water has not yet been used and the quality of the waste water has not yet been determined whether it is used for irrigation purposes. Recycled water especially industrial effluent can be used in agriculture. The aim of the present study was to evaluate the effluent of Romana mineral water Bottling Factory at different concentrations (control, 20, 40, 60, 80 and 100%) for crop cultivation. The pH of the waste water was nearly about neutral but it contained an enough amount of nitrogen, phosphate, chloride, calcium, carbonates, bicarbonates suspended and dissolved solids when compared with fresh water. Accordingly an experiment was conducted to evaluate the effect of effluent on growth and yield of Abelmoschus esculentus(Okra).Different growth parameters such as shoot length, root length, and plant fresh , dry weight was measured.